C юбилеем! - (:unkn) unknown (Запорізький державний медичний університет, 2013)
Alina Romanenko, Full Member of the National Academy of Medical Sciences of Ukraine, Corresponding Member of the National Academy of Sciences of Ukraine, Full Foreign Member of Spanish Royal Academy of Medicine, Member of the International Academy of Pathology, founder and President (1995-2008) of the Ukrainian Division of the International Academy of Pathology, member of the Scientifi c Council of the European Society of Pathology, Doctor of Science in Medicine, Professor, Honored Worker of Science and Technology of Ukraine, Laureate of the State Prize of Ukraine in Science and Technology (2007).
Happy anniversary!
Романенко Алина Михайловна, академик Национальной академии медицинских наук Украины, член-корреспондент НАН Украины, действительный иностранный член Королевской академии медицинских наук Испании, член Международной академии патологии, основатель и Президент (1995–2008) Украинского отделения Международной академии патологии, член Научного Совета Европейского общества патологов, доктор медицинских наук, профессор, заслуженный деятель науки и техники Украины, лауреат Государственной премии по науке и технике Украины 2007 года.
Keywords: патолог